Artificial intelligence by example : develop machine intelligence from scratch using real artificial intelligence use cases - Rothman, Denis (Packt Publishing, 2018)
Artificial Intelligence(AI), gets your system to think smart and intelligent. This book is packed with some of the smartest and easy-peasy examples through which you will learn the fundamentals of AI. You will have acquired the foundation of AI and understood the practical case studies in this book.